Treatment goals in IBD: A perspective from patients and their partners - Niene M.S. Peek-Kuijt; Margaretha J. Aantjes; Marthe Verwey; Leti Van Bodegom-Vos; Andrea E. van der Meulen-de Jong; Jeroen P.W. Maljaars (Elsevier, 2022)
Objective: To identify and compare treatment goals between IBD patients and partners, and how these change upon receiving information. Methods: During a patient information day a self-made survey was distributed before and after a lecture about a physicians' view on treatments goals. Patients and partners were asked for their preferred treatment goals at 6 weeks and at 6 months and could choose between short-term goals (symptom free, improved functioning, better QOL, normal colonoscopy) and long-term goals (prevention of surgery, complications, flares and no steroids). Results: Being "symptom-free" (55.9%) was the preferred goal. Patients with higher disease activity chose more short-term goals (p=0.03) at 6 weeks. Age, gender and education did not affect treatment goals. Partners chose more short-term goals (p=0.03) at 6 weeks. Post-lecture, answers shifter to normal colonoscopy (4.2% versus 18.0%, p=0.001), and a better QOL (21.2% vs 33.3%, p=0.039) as goal at 6-months. Conclusions: Patients' 6-week treatment goals focused on being symptom-free and having a high QOL, especially those patients with high disease activity. Partners chose more short-term goals than patients at 6 weeks. Innovation: General health information can be applied and translated into treatment goals. This may assist in remote shared goal setting and decision making